Language Facilitates Beckham’s Ideas into Meaningful Sayings: Pragmatic Analysis - Meilenia, Libel; Mulia, Vilya Lakstian Catra; Zanah, Sri Wahyuni Samaratul (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
In his speech at UNICEF, David Beckham emphasized the importance of protecting the dreams and aspirations of children. He shared his experience while visiting various countries. As a public figure, Beckham utilizes his popularity to advocate for important issues. His speech at UNICEF is a prime example of how Beckham leverages his platform to have a positively impact and inspire others. This research analyses speech acts as Beckham’s communication strategy to articulate the objective of his speech. The data used are words, phrases, and clauses. The research employs document analysis, where the researchers transcribe Beckham’s speech and divide the transcript into several clauses. These clauses are the used to analyse the speech act utilized in Beckham’s speech at UNICEF. Beckham’s speech proved to be effective in influencing the audience. He utilized his popularity to encourage action in protecting children’s dream. Analysis shows that the speech was not only informative but also successfully generated empathy and prompted concrete actions from listeners.